"One‐pot" random terpolymerization of styrene, isoprene and butadiene with Nd‐based catalyst. Issue 3 (6th May 2013) - Li, Tingting; Hu, Yanming; Zhang, Hongxia; Shi, Zhenghai; He, Gongqiang; Wang, Yurong; Shen, Kaihua; Li, Yang
ABSTRACT Random styrene‐isoprene‐butadiene rubber (SIBR) were achieved with the catalyst system composed of neodymium isopropoxide (Nd(OiPr)3), methylaluminoxane (MAO) and indene. This catalyst proved to be highly effective in cyclohexane even at low [Al]/[Nd] ratio (ca. 50) to give styrene‐rich terpolymer with high number‐average molecular weight (Mn) and narrow molecular weight distribution (Mw/Mn). Indene was critical to improve the coordination of styrene. High temperature was beneficial to increase the yield. Aliphatic solvents (hexane and cyclohexane) achieved a higher Mn of polymer than toluene as a solvent. The glass transition temperature (Tg) and composition of SIBR can be controlled by tuning the feed ratio of monomers. All the products have been fully characterized by NMR spectroscopy, gel permeation chromatograph (GPC), and DSC. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 1772–1777, 2013